2012
DOI: 10.1186/1476-511x-11-45
|View full text |Cite
|
Sign up to set email alerts
|

Fuzheng Huayu recipe prevents nutritional fibrosing steatohepatitis in mice

Abstract: BackgroundFuzheng Huayu recipe (FZHY), a compound of Chinese herbal medicine, was reported to improve liver function and fibrosis in patients with hepatitis B virus infection. However, its effect on nutritional fibrosing steatohepatitis is unclear. We aimed to elucidate the role and molecular mechanism of FZHY on this disorder in mice.MethodsC57BL/6 J mice were fed with methionine-choline deficient (MCD) diet for 8 weeks to induce fibrosing steatohepatitis. FZHY and/or heme oxygenase-1 (HO-1) chemical inducer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Nutritional factors such as high methionine-diet are associated with increased serum homocysteine levels. Extensive studies have shown that a high methionine-diet had awful effects on liver pathophysiology, for instance, oxidative stress, inflammation, lipid metabolism disorders and fibrosis [ 27 , 28 ]. Our observations are in line with previous studies reporting that methionine supplementation increased plasma Hcy levels, triggered oxidative stress of livers and impaired the anti-oxidative enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional factors such as high methionine-diet are associated with increased serum homocysteine levels. Extensive studies have shown that a high methionine-diet had awful effects on liver pathophysiology, for instance, oxidative stress, inflammation, lipid metabolism disorders and fibrosis [ 27 , 28 ]. Our observations are in line with previous studies reporting that methionine supplementation increased plasma Hcy levels, triggered oxidative stress of livers and impaired the anti-oxidative enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of abnormally expressed miRNAs in the important pathologic state of NAFLD is helpful to further understand the molecular mechanism of nonalcoholic fibrosing steatohepatitis. In this study, we evaluated the differentially expressed miRNAs in nonalcoholic fibrosing steatohepatitis induced in mice fed with methionine-choline deficient (MCD) diet 15 16 17 and demonstrated for the first time that miR-146a-5p suppresses activation and proliferation of HSCs in the pathogenesis of nonalcoholic fibrosing steatohepatitis through targeting Wnt1 and Wnt5a and their consequent effectors alpha-smooth muscle actin (α-SMA) and type I collagen (Col-1).…”
mentioning
confidence: 99%
“…Many previous studies also proved the usefulness of network pharmacology in investigating the synergistic molecular mechanisms of the TCM formula [6][7][8]. However, false positive probability of network pharmacology approaches is relatively large, which results in hundreds of active components and their potential target proteins for a TCM formula [9][10][11]. us, we try to combine the network pharmacology approach with known proteomics results in order to reduce the false positive probability.…”
Section: Introductionmentioning
confidence: 99%